Le demi-siècle Lettriste - Letaillieur, François (Paris : Galerie 1900-2000, 1988)
Altmann, Roberto ; Brau, Jean-Louis ; Broutin, Gérard-Philippe ; Canal, Françoise ; Curtay, Jean-Paul ; Dufrene, François ; Dupont, Albert ; Gette, Paul-Armand ; Gillard, Jean-Pierre ; Grimaud, Antoine ; Hachette, Micheline ; Isou, Isidore ; Jessemin, Aude ; etc.
Le demi-siècle Lettriste, Galerie 1900-2000, Paris, 11.04 - 07.05.1988
boek